Optimalisasi Kinerja Karyawan Melalui Kualitas Pelayanan, Fasilitas Kerja dan Kepuasan Kerja - Shely Merlyana; Anis Turmudhi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to evaluate how job satisfaction, work environment, and service quality affect employees' performance at the Puskesmas Kalikajar II Wonosobo. The participants of this research consist of 38 personnel from the Kalikajar II Wonosobo Community Health Centre. This research used multiple linear regression analysis on a sample size of 38 individuals. The saturation sampling method was the sample strategy employed in this study. The questionnaire survey method was employed as the data collection strategy in this study. The study's findings indicate that service quality has a beneficial impact on employee performance, albeit this effect is not statistically significant. Therefore, hypothesis 1 is rejected. Consequently, the performance of workers is unaffected by the kind of service they deliver. The presence of work facilities has a beneficial impact on the facilities. Hypothesis 3 is rejected since job satisfaction has a favorable influence on employee performance, albeit this effect is not statistically significant. This implies that fluctuations in employee work satisfaction do not impact performance of employees, hence supporting hypothesis 2. This implies that enhanced work amenities have the potential to enhance employee productivity, and conversely, improved employee performance may lead to better work employee performance